CESifo World Economic Survey February 2007 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2007)
World Economic Climate: World Economic Climate brightens - Economic Expectations: Both assessments of the current economic situation and economic expectations somewhat improved - Inflation: Expectations for 2007 revised downwards - Interest Rates: Trend of rising interest rates is slowing - Currencies: Western European currencies – euro and UK pound – seen as overvalued - Special Topic: Statistical information in public and political decision making
Keywords: 330